Sex-based differences as a predictor of recovery trajectories in young athletes after a sports-related concussion - Ono, K. E.; Burns, T. G.; Bearden, D. J.; McManus, S. M.; King, H.; Reisner, A. (The American Journal of Sports Medicine, 2016)
Background: To date, few studies have delineated clear sex-based differences in symptom resolution after a sports-related concussion (SRC), and equivocal results have been identified in sex-based differences on baseline assessments.